2017
DOI: 10.1111/echo.13762
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of left ventricular strain analysis in patients with takotsubo syndrome during acute phase

Abstract: Assessment of LV global and segmental longitudinal strain by speckle tracking has important prognostic value in the acute phase of TTS. Additional large-scale studies will be needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…However, echocardiographic indices by STE may be more convenient, inexpensive and distinctive than the variables by CMRI for early detection of subtle abnormalities [14]. In clinical practice, previous studies have reported that STE could provide useful indexes for quantitative evaluation of LV function and suggested that it had higher sensitivity in detecting subtle abnormalities compared to more traditional parameters such as LVEF and wall motion score index [12,30]. Liu et al evaluated the protective effects of ischemic postconditioning on myocardial function using STE and concluded that STE could detect myocardial function improvement in a rabbit model [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, echocardiographic indices by STE may be more convenient, inexpensive and distinctive than the variables by CMRI for early detection of subtle abnormalities [14]. In clinical practice, previous studies have reported that STE could provide useful indexes for quantitative evaluation of LV function and suggested that it had higher sensitivity in detecting subtle abnormalities compared to more traditional parameters such as LVEF and wall motion score index [12,30]. Liu et al evaluated the protective effects of ischemic postconditioning on myocardial function using STE and concluded that STE could detect myocardial function improvement in a rabbit model [31].…”
Section: Discussionmentioning
confidence: 99%
“…The heart rate was obtained by an electrocardiogram (ECG). The LV ejection fraction (LVEF), LV end-diastolic volume (LVEDV), and stroke volume (SV) were calculated by the biplane Simpson's method [12]. The minimal frame rate was 250 per second.…”
Section: Conventional Echocardiographymentioning
confidence: 99%
“…Infrequently, an ECHO is performed prior to CAG in patients with SCAD, and much more often in patients with TTS, a comprehensive study would be necessary for the differentiation of SCAD and TTS. [9][10][11] However, in the spirit of implementing ECHO as early and frequently as possible, we should take advantage of any available information, even if acquired by substandard equipment (handheld ECHO devices), and generated by less experienced operators, than ECHO professionals (physicians working in the Emergency Departments and Intensive Cardiac Care Units). 9,12,13 F I G U R E 1 Images of a 54-year-old woman with SCAD and TTS (from Y-Hassan et al, 6 reproduced with the permission of Wiley Online Library, and with modification of its legend).…”
Section: (Sophocles)mentioning
confidence: 99%
“…That communication included 18 relevant references, provided 19 specific technical points, and 6 recommendations, which could be the basis for the ECHO differentiation—between TTS and ACS, or STEMI, and all of them apply to the differentiation between SCAD and TTS. Both conventional 2D and 3D ECHO, and 2D and 3D speckle tracking should be implemented, to unravel whether a patient, shown eventually to have SCAD, has, in addition, a “TTS component,” in the sense that the observed regional RWMA are more extensive and/or involve myocardial territories beyond the one subtended by a coronary artery, or its branches thereof, revealing SCAD (Figures and ) . Patients with subsequently documented SCAD or TTS present with chest pain and are often quickly referred to the catheterization laboratory for diagnosis, which provides information on the coronary arteries, and some insight about the LV chamber (if a uniplane left ventriculogram is carried out, which is not always the case), in terms of showing classic midventricular or apical ballooning, or showing RWMA territorially discordant with the sites perfused by the coronary vessels revealing SCAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation